Analisis Wacana Media terhadap Pemberitaan Rencana Kebijakan Pajak e-Commerce - Rostamaji Korniawan (Institut Pertanian Bogor, 2019)
This research is intended to examine how far the communication plan of the government issued tax policies for e-commerce business actors. To study it, this study uses media discourse analysis methods, especially online media, to report on the government's plan to impose e-commerce taxes. Observations were made in the period 2017 to mid-2018. From the results of observations made, the results of the study found that the government and the public were ready and supported the issuance of e-commerce tax policy. Online media which are the object of observation in research see the substance of the discourse of the news delivered in an informative and supportive manner, especially online media which also has an operational network for publishing print media. Thus it can be concluded that the communication of the government's plan regarding the implementation of e-commerce taxation whose initiation began in 2016 seems to have been done well.